The Utilization of Coconut Coir as Supplementary Feed for Beef Cattle Production - Limbang Kustiawan Nuswantara; Sunarso Sunarso; Mukh Arifin; Agus Setiadi (Caraka Tani: Journal of Sustainable Agriculture, 2022)
High feed price is a major problem in the production of beef cattle. Therefore, this study aims to determine coconut coir's technical and economic potential for beef cattle feed. This is an in vivo and in vitro study that involved 95 days trial period and 16 male Brahman crossbreed cattle weighing 134±12.1 kg. The coconut coir was fermented using buffalo rumen liquid and was termed fermented coconut coir (FCC). A randomized block design was used in this research, including four feed treatments, namely complete feed D1 using 15% FCC, D2 using 20% FCC, D3 using 25% FCC and D4 using 30% FCC. The parameters observed were technical performance (protein, dry and organic matter intake), ruminal fermentability, purine derivatives and economic performance. The data were analyzed using analysis of variance and Duncan's multiple range test for posthoc multiple comparisons. The results showed that the intake of beef cattle feed D1, D2 and D3 was higher than D4. Furthermore, the digestibility of D1, D2 and D4 was higher than D3. The purine derivatives of D2 were the highest but not significantly different (P > 0.05) from D1 and D4. In addition, the ruminal fermentability was not significantly different (P > 0.05) among treatments. Moreover, the beef cattle feed on D2 had the best economic performance. The performance results showed that ruminal fermentability, purine derivatives and economic performance of D2 (20% FCC) gave the best results but were not statistically different (P > 0.05) from other variables. Conclusively, coconut coir can be used as beef cattle feed without causing health problems.